Literasi abu-abu dalam perpustakaan - Suwandi Suwandi (UIN Sumatera Utara, 2017)
The more rapid rain of information that occurs, will increase the awareness of the user to literate for the sake of reviewing an outstanding information that has not been ascertained the truth. The development and use of technology also makes it easy for librarians to publish gray literacy to users, especially students in supporting their formal and non-formal learning process, so that gray literacy is used to the maximum extent by the users and be aware of the importance of the value contained in the ash literacy -ash.